Sports injuries int the EU countries in view of the 2004 Olympics - Harvesting the information from existing databases - Petridou, E. (2002)
The project "Sports Injuries in the EU Countries in View of the 2004 Olympics: Harvesting the Information from Existing Databases, proposed by the Center for Research and Prevention of Injuries among the Young (CE.RE.PR.I.) and approved for funding by DG SANCO, aims to address the problem of sports injuries among European Member States. The project is schematically divided into two phases: Phase I: The goals of the first phase of the project were to review the current knowledge in the field, ascertain the burden of sport injuries in EU member states and analyse the currently available information. Phase II: The second phase of the project was aiming to identify conditions that increase the risk for sports injuries and investigate the effectiveness of currently used prevention strategies. During the first phase of the project the current knowledge in the literature was reviewed and an operational definition that could provide comparability of data was developed. The overall magnitude of the problem was assessed through a set of public health indicators. For instance, on the basis of the indicated rates, each year more than 700 individuals die in the EU from a sports injury whereas approximately 700.000 are hospitalised. Finally the profile of injuries was described through EHLASS data that were provided by the participating countries. This report provides results from Phase II of the sports injury project that is aiming to: Fully exploit the potential of the former EHLASS to identify risk factors for sports injuries, Identify situation and conditions conducive to increasing risk taking with special emphasis given to the issue of performance enhancing substances, Assess the effectiveness of currently used injury prevention strategies, develop recommendations and identify gray areas that need clarification and further research, and Create a EU network of sports injuries experts. In support of this effort, the potential and the possibility to utilize the former EHLASS sports injury data, as explored during phase I, were evaluated in order to identify risk factors for sports injuries. Analysis of the "free text" was performed aiming to elicit detailed information that is not captured in the coding system. Situations and conditions that increase risk(s) for sports injuries with special emphasis on performance enhancing substances were identified through an anonymous questionnaire that was self-administered to 2650 tertiary education students in five EU countries and Israel. The effectiveness of currently used prevention strategies for the prevention of sports injuries was assessed first on the basis of a literature review and subsequently by soliciting the fragmented and diverse EU experience on the subject from thirty two sports injuries experts. The potential for the creation of a EU Network of Sports Injuries Experts was investigated and is responsive to recent recommendations of the partners meeting held in Paris (28/02/02). "Free text analysis" revealed three additional injury prevention risk factors. They have been cited in the literature but had not been identified through the existing coding system. These include: 1) environmental factors, 2) personal equipment and 3) psychological factors. Additionally, suggestions were made to interviewers on how to write more accurate and useful reports for future analyses of free text descriptions, by providing specific examples and keywords (available in a newsletter electronic form). Experts participating in the sports injury prevention survey expressed their opinion on several gray areas, based on their different background and working experience. By combining the different reports, several issues were identified where there was consensus and several others where additional research is recommended. The doping survey showed that doping among tertiary education students is endemic, though not hyper-endemic, without striking variation among the participating countries. Men are more likely than women to make use of performance enhancing substances. Body mass index is positively associated with doping admission. The frequency of excess drinking of alcoholic beverages, coffee drinking, and to a lesser extent tobacco smoking is positively associated with doping. Experts participating in the EU Network came from various disciplines, such as physicians, epidemiologists, statisticians, coaches, and athletic reporters. The EU added value from the creation of an expert`s intranet will be: a) network can be the basic resource to identify experts in this field, b) strengthening the communication among prestigious experts in sports injuries prevention, c) collaboration in the development of sports injury prevention Research Agenda(s), and d) avoidance of duplication of work in the field of sports injuries prevention. A core inventory of experts in the field of sports injuries prevention has been implemented consisting of sixteen experts from four countries (see attached Newsletter for injuries prevention). Fifteen of those are also included in the electronic version of the inventory, the Internet Forum the Center for Research and Prevention Among the Young (CE.RE.PR.I) has developed, after their written consent. In this Internet site only members (with username and password) will be able to enter (login) and communicate with their peers. The Internet Forum is located at http://www.inhealth.gr/sip (temporary web address). This project brought to light the fragmented and diverse EU experience regarding sports injury prevention and provided the basis for creation of a EU Network of Sport Injuries Experts that could facilitate collaboration in future sports injuries research activities. The Network could also be responsive in a timely manner to issues and concerns that require an immediate response. The results and findings of this project, presented in the printed and electronic newsletters, are available and will be distributed to interested individuals and groups. The knowledge derived from this project will help develop policies at the EU level and design more effective injury prevention strategies, programs and activities in the future that will help reduce the burden of sports injuries.